Distal Radius Fractures: An Epidemiological Review - Koo, Kevin O T (Orthop Surg, 2013)
OBJECTIVE: Distal radius fractures are among the most common fractures encountered in clinical practice. Although multiple epidemiological studies have been done in Western populations, there is a lack of data within Asia. Our study aims to fill this knowledge gap. METHODS: This study included all patients aged 16 years and above with distal radius fractures seen between November 2008 and May 2009 by the Department of Hand and Reconstructive Microsurgery at the Singapore National University Hospital. A retrospective analysis was done. Information captured included clinical data, hand dominance, AO classification of fractures, mechanism of injury, associated injuries as well as treatment modalities. RESULTS: Of the 431 fractures, 238 were males, 181 were females. These fractures occur at all ages, peaking at the 50 to 60 years age group. The peak incidence of distal radius fractures in females occurred in the perimenopausal age group, whereas the incidence for males peaked between age of 30 to 50. By AO classification, 53% were type A; 13% were type B and 32% were type C. A fall on the outstretched hand from a standing position is the most common mechanism of injury. As the intensity of the injury mechanism increased, the percentage of type C fractures increased correspondingly. Older patients were more likely to be treated conservatively compared to younger patients. AO severity classification correlated well with the clinician's decision to surgically fix the fracture. No correlation between hand dominancy and fracture site found was found. CONCLUSION: We compared our data with that of previous similar studies, and found similarities as well as differences in results. Nevertheless, the epidemiogical data gathered in this study has added to our knowledge of distal radius fractures in an Asian population.